An analysis of the potential for mobile auctions in China. (1st December 2008) - Wang, Shuo; Barnes, Stuart J.
The growth of mobile communications and online auctions in China has been rapid. This article examines the acceptance of mobile auctions – a product of the convergence of these trends. The methodology is based on the testing of a statistical model founded on the technology acceptance literature. The findings support the Technology Acceptance Model and indicate the importance of trust (i.e. Trusting Beliefs and intentions), social influence (i.e. Social Image) and individual characteristics (i.e. age, knowledge and enjoyment) in influencing the acceptance of m-auctions. The article rounds off with a summary and conclusions, examining the implications for future research and practice.